2014
DOI: 10.1155/2014/730375
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Interstitial Duplication of 8q22.1–8q24.3 Associated with Syndromic Bilateral Cleft Lip/Palate

Abstract: We present a rare case of 8q interstitial duplication derived from maternal balanced translocations in a patient with bilateral cleft lip and palate in syndromic form associated with other congenital malformations. G-banding cytogenetic analysis revealed a chromosomal abnormality in the form of the karyotype 46,XX der(22)t(8;22)(q22.1;p11.1)mat. Chromosome microarray analysis evidenced a 49 Mb duplicated segment of chromosome 8q with no pathogenic imbalances on chromosome 22. Two siblings also carry the balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…ID is caused by perturbations in the significant biological functions that impact cellular networks present in different regions of the CNS. We identified the influence of each of the 44 prioritized genes ( Supplementary Table S5 ) in different tissues and found that these genes are mainly expressed in the CNS when compared with other tissues in humans ( Figure 3 ) [ 14 , 16 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…ID is caused by perturbations in the significant biological functions that impact cellular networks present in different regions of the CNS. We identified the influence of each of the 44 prioritized genes ( Supplementary Table S5 ) in different tissues and found that these genes are mainly expressed in the CNS when compared with other tissues in humans ( Figure 3 ) [ 14 , 16 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, six genes from the duplicated region 18p11.32-p11.21 are highly expressed in several regions of the CNS, from which three of them (LAMA1, MYOM1, and TGIF1) were duplicated in individuals with ID [ 18 , 19 , 20 ]. Furthermore, patients with duplication of 8q24.13q24.3 region involving the KCNQ3, PTK2, ASAP1, and NDRG1 genes, which are widely expressed in CNS, presented ID [ 14 , 16 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations